Application prospects of threaded joint of armature - Radkevych, A. V.; Netesa, A. N. (Science and Transport Progress, 2014)
Purpose. One of the main technological operations of buildings construction on the basis of monolithic frame systems is the production of mesh reinforcement. The current interest is the new ways specification of advanced bonding armature techniques without reliability weakness and design of the building in whole, as well as the finding of use prospects of screw-threaded joint of armature as the most technological and economic method of re-bars joints. Methodology. Advantages and disadvantages analysis of existing rebar compound technologies was implemented by couplings of different types and constructions. The most promising vertical constructions for the vertical bars joints in frameworks were determined. Findings. Researches of existing technologies of rebar joints by the couplings of different construction were carried out. The installation method of mesh reinforcement of vertical structural elements with the use of the special catching devices was developed. It allows considerably accelerating installation of mesh reinforcement. Originality. Regularity of labor intensiveness change of mesh reinforcement installation of columns at armature joint in vertical position by threaded couplings with the help of catching devices using special construction was determined. This allows substantially reducing the labor expenditures during installation of these elements. Dependency of labor intensiveness and cost of lap welding armature joints, by tub-seam welding and by thread coupling depending on its diameter was designated. Regularity of labor intensiveness changes of installation at armature joints by different methods taking into account preparatory works was defined. Practical value. The analysis of mechanical armature joints techniques was conducted. It will allow selecting methods of armature joints to increase the speed of construction works more economical and effective.